2012
DOI: 10.1007/s00262-012-1317-2
|View full text |Cite
|
Sign up to set email alerts
|

Sipuleucel-T immune parameters correlate with survival: an analysis of the randomized phase 3 clinical trials in men with castration-resistant prostate cancer

Abstract: PurposeSipuleucel-T, the first FDA-approved autologous cellular immunotherapy for treatment of advanced prostate cancer, is manufactured by activating peripheral blood mononuclear cells, including antigen presenting cells (APCs), with a fusion protein containing prostatic acid phosphatase. Analysis of data from three phase 3 trials was performed to immunologically characterize this therapy during the course of the three doses, and to relate the immunological responses to overall survival (OS).MethodsSipuleucel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
241
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 230 publications
(252 citation statements)
references
References 32 publications
5
241
1
1
Order By: Relevance
“…For example, the ability to identify nonresponders within the first 3 mo of treatment could enable clinicians to adjust treatments rationally many months to years before clinical assessments (e.g., tumor burden, PSA levels) become reliable indicators of an effective response. Although previous investigations of immune responses to vaccination have found potential associations with clinical responses (1,5,6,10,11), no clinically validated biomarker of efficacy is available for any cancer vaccine. Detailed investigations of T-cell responses, humoral responses to protein antigens, and immunosuppressive T-regulatory cells have not accounted consistently for variation in survival benefit among patients (2,3,5,6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the ability to identify nonresponders within the first 3 mo of treatment could enable clinicians to adjust treatments rationally many months to years before clinical assessments (e.g., tumor burden, PSA levels) become reliable indicators of an effective response. Although previous investigations of immune responses to vaccination have found potential associations with clinical responses (1,5,6,10,11), no clinically validated biomarker of efficacy is available for any cancer vaccine. Detailed investigations of T-cell responses, humoral responses to protein antigens, and immunosuppressive T-regulatory cells have not accounted consistently for variation in survival benefit among patients (2,3,5,6).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, studies aimed at identifying new biomarkers often lack controls necessary to assess whether a particular candidate biomarker is vaccine specific or is an epiphenomenon arising from nonspecific effects of disease progression (9). Although several promising studies have linked postvaccination immune responses with favorable clinical responses (1,5,6,10,11), none to date has led to a validated companion diagnostic. Therefore new clinically relevant biomarkers of vaccine efficacy are urgently needed.…”
mentioning
confidence: 99%
“…Additionally, 39.5% (60/152) of sipuleucel-T treated patients showed a response to PAP, vs. 5.7% (4/70) of control patients. 4 The humoral response was still detectable 6 months after treatment, with anti PA2024 and anti PAP IgG antibodies continuing to increase after 26 weeks. Sipuleucel-T treated patients who developed at least one peripheral immune Keywords: GU malignancies, immune response, prostate cancer, urology, sipuleucel-T response (T-cell proliferation, IFNg ELI-SPOT or antibody production) to PA2024 or PAP were also associated with significantly better OS (HR D 0.47) (95% CI: 0.29-0.78; P D 0.003).…”
Section: Evaluating Immune Responses After Sipuleucel-t Therapymentioning
confidence: 94%
“…Sipuleucel-T treated patients who developed at least one peripheral immune Keywords: GU malignancies, immune response, prostate cancer, urology, sipuleucel-T response (T-cell proliferation, IFNg ELI-SPOT or antibody production) to PA2024 or PAP were also associated with significantly better OS (HR D 0.47) (95% CI: 0.29-0.78; P D 0.003). 4 To understand the effect of sipuleucel-T not just peripherally, but on the tumor microenvironment, Fong et al conducted a phase II clinical trial of sipuleucel-T in the neoadjuvant setting for 37 patients with localized prostate cancer, who were eligible for radical prostatectomy. 5 In this study, they found that prostatectomy specimens of patients treated with sipuleucel-T showed more than a 3 fold increase in infiltrating CD3C, CD4CFOXP3-and CD8C T cells, compared with pretreatment biopsies.…”
Section: Evaluating Immune Responses After Sipuleucel-t Therapymentioning
confidence: 99%
“…A survival benefit can be observed in the absence of an objective response, as demonstrated by the efficacy of sipuleucel-T in prostate cancer. 88 Moreover, the immune checkpoint inhibitor, ipilimumab, showed distinct radiological response patterns in metastatic melanoma (long stabilization, pre-response flare-up, and delayed response). An early response might not always be a good surrogate for survival.…”
Section: Counteracting the Immunosuppressive Environmentmentioning
confidence: 99%